Предмет:
АлгебраАвтор:
yandelfmduПроизводная функции равна y' = (e^(-3x))*(1 - 3x).
В точке х = -1 она равна y' = 4e³.
Функция при х = -1 равна y(-1) = -e³+ 4.
Тогда у(кас) = y'*(x - xo) + y(-1) = 4e³*(x - (-1)) + (-e³ + 4) = 4e³x + 3e³ + 4. (A).
Автор:
saraizn7yДобавить свой ответ
Предмет:
МатематикаАвтор:
ezequielfernandezОтветов:
Смотреть
Предмет:
Русский языкАвтор:
lisa65Ответов:
Смотреть
Предмет:
Английский языкАвтор:
soniamullinsОтветов:
Смотреть
Предмет:
Английский языкАвтор:
angel15Ответов:
Смотреть